RESPONSE OF OFFERED FERMENTED PURPLE SWEET POTATO (Ipomoea batatas L) SKIN AS ANTIOXIDANT COMPOUND IN DIETS IMPROVED MEAT QUALITY OF BALI DUCK - Tjokorda Gede Belawa Yadnya; Ida Bagus Gaga Partama; Anak Agung Ayu Sri Trisnadewi; Ni Made Suci Sukmawati (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2015)
This experiment was carried out to study the response of offered fermented purple sweetpotato(Ipomoea batatas L) skin as antioxidant compound in diets on quality meat quality ofbali duck. Five treatment diets were used in a completely randomized design (CRD) consistedof control diet A (diet without containing purple sweet potato skin), diet B containing 10%purple sweet potato skin, diet C containing 10% fermented purple sweet potato skin, diet Dcontaining 20% purple sweet potato skin and diet E containing 20% purple sweet potato skin.Each treatment consisred of four replications and each replication consisted of five ducks.Variable s observed in this study meat quality with obyective method consisted meat colour,water concentration, water holding capacty (WHC), pH, and cooking loss. Organolepticquality consisted colour, smell, taste, texture, and to receive of whole. Anthocyanin, proteinand crude fibre consumption. In general, the showed that offered fermented purple sweetpotato skin in diets were significantly (P<0,05) increased the meat colour, water holdingcapacity, and pH, but on water concentration was not significantly (P>0,05) and on cookingloss was deceased significantly P<0,05). also could be increased organoleptic meat qualitywere colour, smell, taste, texture, and to receive of whole(P<0,05). Offered fermented purplesweet potato skin in diets could be increased anthocyanin and crude protein consumption.However, crude fibre consumption did not affected compared with the treament in A diet. Itwas concluded that the fermented purple sweet potato (Ipomoea batatas L) in diets couldimprove meat quality of Bali duck.